Back to stay - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Eastern Africa Journal of Rural Development (EAJRD) Published by the Department of Agricultural Economics & Agribusiness, Makerere University, Uganda, biannual journal. Free for members of the Eastern Africa Agricultural Economics Society. Information o